Antioxidant activity and total flavonoid content of honeys - Czipa, Nikolett; B. Varga, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2010)
The influence of honey on human health has been known since ancient times. Different components, like vitamins, amino-acids, enzymes, and the so called antioxidant activity of the honey play role in this effect, and also in the excellent quality. The aim of present study was to determine the total antioxidant activity and the flavonoid content of some honey samples. These two parameters are widely studied, and a lot of data can be used to compare and analyse. On the basis of them we can state that our results are quite similar than those we can find in literature. Characteristic feature of the examined honey samples is, that the antioxidant activity increased with the darkening of the colour. The lowest antioxidant activity and flavonoid content was produced by the acacia honeys with greenish shade of colour. The highest values was found in the very dark honeys (forest, sage, golden rod). The only exception was the coriander honey, where despite of its lighter colour, very high antioxidant activity was measured.